C.1 - Schumpeter, Joseph A. (New York, 1963)
At the time of his death in 1950, Joseph Schumpeter--one of the great economists of the first half of the 20th century--was working on his monumental History of Economic Analysis. A complete history of efforts to understand the subject of economics from ancient Greece to the present, this book is an important contribution to the history of ideas as well as to economics. Although never fully completed, it has gained recognition as a modern classic due to its broad scope and original examination of significant historical events. Complete with a new introduction by Mark Perlman, who outlines the structure of the book and puts Schumpeters work into current perspective, History of Economic Analysis remains a reflection of Schumpeters diverse interests in history, philosophy, sociology, and psychology. Major topics include the techniques of economic analysis, contemporaneous developments in other sciences, and the sociology of economics; economic writings from Plato and Aristotle up through the time of Adam Smith, including the medieval scholastics and natural-law philosophers; the work of Malthus, Mill, Ricardo, Marx, and the important European economists; the history, sociology, psychology, and economics of the period 1879-1914; and modern economic developments. Schumpeter perceived economics as a human science, and this lucid and insightful volume reflects that perception, creating a work that is of major importance to the history of economics.
Keywords: Economics history